2007
DOI: 10.1111/j.1365-3024.2007.01009.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the immune response against Strongyloides venezuelensis in antigen‐immunized or previously infected mice

Abstract: The present study was carried out to investigate the immune response against Strongyloides venezuelensis infection in Balb/c mice previously immunized with larva-antigens or primed with live-larvae. Our results indicate that all primed mice developed a strong protection against challenge infection that remained active for 45 days. In mice primed with live-larvae the challenge infection resulted in great reduction of migrating larvae and the worms were completely eliminated from the small intestine before matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
24
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 39 publications
7
24
0
6
Order By: Relevance
“…The more rapidly effective expulsion of S. venezuelensis observed in wild-type mice in the secondary infection is consistent with prior work indicating that adaptive immunity enhances host resistance to this nematode (39,40,45). To investigate the importance of various potential effector mechanisms in orchestrating immune responses to S. venezuelensis, we examined primary and secondary infections in mice deficient in different components of innate or adaptive immunity.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The more rapidly effective expulsion of S. venezuelensis observed in wild-type mice in the secondary infection is consistent with prior work indicating that adaptive immunity enhances host resistance to this nematode (39,40,45). To investigate the importance of various potential effector mechanisms in orchestrating immune responses to S. venezuelensis, we examined primary and secondary infections in mice deficient in different components of innate or adaptive immunity.…”
Section: Resultssupporting
confidence: 78%
“…We also examined whether MCs and/or basophils contribute to cessation of S. venezuelensis egg excretion during secondary infections. Several studies indicated that, in secondary nematode infections of wild-type mice, the larvae can be trapped in the skin and lungs before reaching the intestines, as reported for S. venezuelensis (39)(40)(41), Strongyloides ratti (41), and Nippostrongylus brasiliensis (42)(43)(44). In this study, we assessed fecal egg numbers as an indicator of whether larvae could reach the intestines and then produce eggs.…”
Section: Resultsmentioning
confidence: 99%
“…Strongyloides venezuelensis, a murine intestinal parasite, has been used as a model for understanding the host-parasite relationship in strongyloidiasis (Fernandes et al 2008). The aim of this study was to evaluate whether S. venezuelensis coinfection can modulate M. bovis infection, affecting IL-17A production and granuloma formation in BALB/c mice.…”
mentioning
confidence: 99%
“…Vermiculite is a compound formed by hydration of basaltic mineral; it has been used as a substrate for fecal culture, particularly in veterinary parasitology, as it has the advantages of being similar to soil and costing less [3][4][5][6][7] . It has also been used for growing insect 8 or nematodes larvae in order to evaluate the larvicidal effects of fungi [9][10][11][12] .…”
mentioning
confidence: 99%